The Relationship of Education and Regional Income Level on Environmental Quality: Empirical Evidence from High Populated Country - Fakhri Adrian; Khoirunurrofik Khoirunurrofik (Department of Urban and Regional Planning, Diponegoro University, 2021)
Indonesia is committed to implementing a sustainable development agenda by considering its quality and maintaining economic growth by improving public education and regional income. This study aims to estimate the relationship between education and regional income level with the environmental quality of Indonesian provinces. By applying the descriptive analysis and panel data regression, it is observed that regions with a high-level level of education and income are likely to have low environmental quality, which shows that education level has a negative relationship with environmental quality. In contrast, income level has no relationship with environmental quality. The empirical estimation revealed that higher education and regional income correlate with a lower level of environmental quality. It implied that the regional development in Indonesia has been at the cost of environmental degradation. It advised establishing an incentive and disincentive mechanism for economic actors to utilize energy resources and environmentally friendly production technology and bring the country into a sustainable development direction.